Detailed design of product oriented manufacturing systems - Silva, Sílvio Carmo (2006)
This paper presents a procedure for the detailed design and redesign of manufacturing systems within a framework of constantly fitting production system configuration to the varying production needs of products. With such an approach is achieved the design of Product Oriented Manufacturing Systems – POMS. This approach is in opposition to the fitting, before hand, of a production system to all products within a company. In this case is usual to adopt a Function Oriented Manufacturing System - FOMS, which, rarely require reconfiguration and apparently can deal with such a variety. The detailed design depart from conceptual manufacturing cell configurations and develops from there, through conceptual cell instantiation, the required detailed manufacturing system configuration needed for efficiently and effectively manufacture a product or a family of similar products. Therefore manufacturing requirements of products, based on available or accessible human resources and technology, i.e. manufacturing resources and know-how, as well as production demand are essential inputs to the design of suitable manufacturing configurations for the range of products to manufacture in a given period.